Strategy for accelerating the realization of climate-smart agriculture using a circular economy perspective approach - Prajanti, Sucihatiningsih Dian Wisika; Soesilowati, Etty; Daud, Dalila (Edelweiss Applied Science and Technology, 2025)
This research aims to accelerate the realization of Climate Smart Agriculture (CSA) with a Circular Economy Perspective Approach. The research was conducted in Kopeng Village, Getasan District, Semarang Regency, Central Java. The sampling technique used in this research was the purposive sampling method to select research personnel. The first analytical method in this research is Mactor analysis. The second data analysis method used in this research is ANP (Analytic Network Process). The research results show that the strategy to accelerate the realization of Climate Smart Agriculture (CSA) using a circular economy perspective requires strong collaboration and synergy between stakeholders/actors. The stakeholders who have the strongest role and influence are organic farmers, research institutions, and universities. Efforts to realize climate-smart agriculture based on a circular economy have the main strategic objectives of increasing agricultural productivity amidst uncertain climate change and reducing farmers' dependence on the use of chemical inputs. The strategic priorities in realizing climate-smart agriculture based on a circular economy are selecting plant varieties that are resistant to extreme weather and improving water resource management.